2012
DOI: 10.1111/j.1365-263x.2012.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral midazolam–ketamine better than midazolam alone for sedation of young children: a randomized controlled trial

Abstract: BACKGROUND.  There is a lack of clinical trials on paediatric dental sedation. AIM.  We investigated whether young children's behaviour improves during dental treatment with oral ketamine/midazolam compared with midazolam alone or no sedation. DESIGN.  Healthy children under 36 months of age, presenting early childhood caries were randomly assigned to receive protective stabilization plus: combined oral midazolam (0.5 mg/kg) and ketamine (3 mg/kg) (MK), or oral midazolam (1.0 mg/kg) (MS), or no sedative (PS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…The results of this study, despite the limitations in the statistical significance, show families in need of social skills but, on the other hand, a beneficial effect of conscious sedation to reduce the suffering of the preschool child in the dentist’s chair, as already shown [20]. Thus, parenting practices should also be addressed by a multidisciplinary health care team for the child in need of elective procedures under pharmacological intervention.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The results of this study, despite the limitations in the statistical significance, show families in need of social skills but, on the other hand, a beneficial effect of conscious sedation to reduce the suffering of the preschool child in the dentist’s chair, as already shown [20]. Thus, parenting practices should also be addressed by a multidisciplinary health care team for the child in need of elective procedures under pharmacological intervention.…”
Section: Discussionsupporting
confidence: 55%
“…So, it was not possible to compare the two sedative regimes regarding their association with children’s behavior and parental educational social skills. Another investigation showed the superiority of midazolam/ketamine for children’s behavior management when compared with midazolam alone, although less cooperative behaviors could also be observed in children that received ketamine [20]. In fact, the body of evidence points out to the efficacy and safety of ketamine in pediatric procedural sedation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Second, both groups in the present study received an association of midazolam and ketamine, which has been proved effective in moderate sedation in both pediatric and dental settings [22, 23]. Other trials associated sevoflurane/nitrous oxide with intravenous midazolam [10], or only compared sevoflurane/nitrous oxide with nitrous oxide [9, 12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that combined ketamine-midazolam provided better results then midazolam alone for sedation of young children [Moreira et al, 2013]. But, children patients younger then 10 years receiving intravenous ketamine along with midazolam display more pronounced adverse effects [Wathen et al, 2000].…”
Section: Evaluation Of the Effect Of Midazolam And Ketoconazole On Kementioning
confidence: 99%